PENGARUH TANGGUNG JAWAB KERJA, LINGKUNGAN KERJA NON FISIK DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI SATUAN POLISI PAMONG PRAJA KABUPATEN LABUHANBATU - Joni Kopter; Ade Parlaungan Nasution; Muhammad Ali Al Ihsan (Bajang Institute, 2022)
This research was conducted on employees of the Pamong Praja Police Unit of Labuhanbatu Regency, with the aim of determining the influence of work responsibility, work environment and job satisfaction on the work productivity of staffers. This research uses quantitative methods with classical assumption test analysis techniques, multiple linear regression tests, hypothesis tests and determination coefficient tests. In order to facilitate the analysis process, an auxiliary analysis tool in the form of IBM SPSS 25 Software was used. This study has the following results: 1) Work responsibility has a positive and significant effect on the work productivity of employees in the Pamong Praja Police Unit, Labuhanbatu Regency; 2) The work environment has a positive and significant effect on the work productivity of employees in the Labuhanbatu Regency Civil Service Police Unit; 3) Job satisfaction has a positive and significant effect on employee work productivity in the Labuhanbatu Regency Civil Service Police Unit